Ultrafast time-resolved quantum cascade laser diagnostic for revealing the role of surface formate species in the photocatalytic oxidation of methanol. Issue 16 (24th July 2020) - Schnee, Josefine; Daturi, Marco; El-Roz, Mohamad
Abstract : QCL-assisted operando FT-IR spectroscopy revealed the role of surface formate species in the photocatalytic oxidation of methanol over TiO2 . Abstract : In the present work, a new quantum cascade laser (QCL)-assisted operando FT-IR setup was used to obtain direct insight into the relationship between the overall catalytic performance of TiO2 photocatalysts in the gas phase photooxidation of methanol at 25 °C, and the kinetics of intermediate surface formate species. Apparent rates of formation ( R app, f ) and reaction ( R app, r ) of surface formates over three different TiO2 photocatalysts (P25, commercial anatase, and homemade anatase) have been determined through UV on–off cycles under flowing methanol and oxygen. We show that the R app, r follows the same trend as the overall catalytic activity in terms of total yield of methylformate and carbon dioxide, namely the following: TiO2 P25 ≈ commercial anatase > homemade anatase. So, the faster the reaction of the surface formates, the higher the catalytic methanol oxidation activity. Thereby, we demonstrate, to our knowledge for the first time, the direct relationship between the conversion of surface formate species and the catalytic performance of the photocatalysts. Through photocatalytic tests without oxygen in the reaction feed, we also show that the crystallinity of TiO2 impacts the availability of its lattice oxygen to contribute for both the formation and conversion of formate species. Indeed, the absence of flowing oxygen reduces the R app, f over TiO2 CA by a factor 2 while it does not affect that over TiO2 P25, and it reduces the R app, r over TiO2 CA about 4 times more than that over TiO2 P25.